Building Information Modelling (BIM) uptake: Clear benefits, understanding its implementation, risks and challenges. (August 2017) - Ghaffarianhoseini, Ali; Tookey, John; Ghaffarianhoseini, Amirhosein; Naismith, Nicola; Azhar, Salman; Efimova, Olia; Raahemifar, Kaamran
Abstract: Rapid advancement of technology continues to leverage change and innovation in the construction industry. Continued digitization of the industry offers the opportunity to totally reinvent contemporary construction design and delivery practice for future development. Building Information Modelling (BIM) within the context of Architecture, Engineering & Construction (AEC) has been developing since the early 2000s and is considered to be a key technology. Despite major technical advancements in BIM, it has not been fully adopted and its definitive benefits have not been fully capitalized upon by industry stakeholders. The lack of widespread uptake of BIM appears to be linked to the risks and challenges that are potentially impeding its effectiveness. This paper aims to discuss the reality of BIM, its widespread benefits and current level of uptake. The risks and challenges associated with the adoption of BIM, as well as recommendations regarding how future BIM adoption could be developed are also highlighted.